ANALYSIS OF STUDENT CHARACTERISTICS THROUGH NON-COGNITIVE DIAGNOSTIC ASSESSMENT AS THE BASIS FOR THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN GRADE IV OF ELEMENTARY SCHOOL - Eneng Ani Wiliani; Mudopar (Cirebon International Conference on Education and Economics Proceeding, 2024)
Non-cognitive diagnostic assessment has become the main concern to find out how the characteristics of each student are, this is an effort to improve learning outcomes that are centered and on the side of students, so that students can be facilitated according to their characteristics. This article reviews the importance of using non-cognitive diagnostic assessments that aim to create a differentiated learning environment, learning facilitated by educators according to the characteristics of each learner, this can support the improvement of all the potential that students have, because each learner has their own uniqueness, and they have the right to succeed in their education. So it is very important for educators to know what the characteristics of the students they will face.